2004
DOI: 10.1063/1.1819988
|View full text |Cite
|
Sign up to set email alerts
|

Energy-band alignments at ZrO2∕Si, SiGe, and Ge interfaces

Abstract: The energy-band alignments for the ZrO 2 / Si, ZrO 2 /Si 0.75 Ge 0.25 , and ZrO 2 / Ge interfaces have been studied using x-ray photoemission. The valence-band offsets of ZrO 2 / Si, ZrO 2 /Si 0.75 Ge 0.25 , and ZrO 2 / Ge interfaces are determined to be 2.95, 3.13, and 3.36 eV, respectively, while the conduction-band offsets are found to be the same value of 1.76± 0.03 eV for three interfaces. The upward shift of valence-band top accounts for the difference in the energy-band alignment at three interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…The sX gap is close to experiment now. The valence band is 5.8 eV wide in sX compared to an experimental value of 6.5 eV [58]. The band dispersions in sX and GGA are quite similar.…”
Section: Band Structures By Sxmentioning
confidence: 53%
See 1 more Smart Citation
“…The sX gap is close to experiment now. The valence band is 5.8 eV wide in sX compared to an experimental value of 6.5 eV [58]. The band dispersions in sX and GGA are quite similar.…”
Section: Band Structures By Sxmentioning
confidence: 53%
“…2(a) shows the bands of the cubic (c-) phase of ZrO 2 . The calculated band gap is 5.34 eV, compared to an experimental value of Table 1 Calculated minimum band gaps for the GGA, sX and WDA methods in eV, compared to those from B3LYP [29 -32] and GW [16 -25] [57,58] and a GGA band gap of 3.4 eV. The sX gap is close to experiment now.…”
Section: Band Structures By Sxmentioning
confidence: 58%
“…Significant research has been conducted on the high-j gate dielectrics such as HfO 2 , ZrO 2 , and Al 2 O 3 grown on (100)Ge, [10][11][12][13][14][15][16][17][18] (110)Ge, 1,15,16 and (111)Ge. 15,16 Among the new high-j dielectric materials, BaTiO 3 (BTO) directly grown on semiconductors has attracted attention for nonvolatile single transistor memory, 19 to reduce the susbthreshold swing and increase the on-current of a transistor.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the carrier conduction behavior, the energy band diagram of the structure is presented. According to the reported results by Wang et al [18] and Zheng et al [24], we found that the valenceband (conduction-band) offset of ZrO 2 /n-Si interfaces is 2.95 (1.76) eV, the band gap of ZrO 2 (Si) is 5.82 (1.11) eV and the electron affinity of ZrO 2 is 1.64 eV. The energy-band alignment for Au/ZrO 2 /n-Si interfaces is shown in Fig.…”
Section: Resultsmentioning
confidence: 64%
“…1 shows the PL spectra of the ZrO 2 (ZrO 2 :PVA) thin film. We used a Ne-Cu laser (the 248.6 nm line) as an excitation source and the energy (4.99 eV) of Ne-Cu laser is lower than the band-gap energy (5.82 eV [18]) of the ZrO 2 film. The PL excitation spectra of the broadband emission of ZrO 2 films were recorded in the energy range of 2.0-4.5 eV.…”
Section: Methodsmentioning
confidence: 99%